2018
DOI: 10.1111/nyas.13569
|View full text |Cite
|
Sign up to set email alerts
|

Update on management of diabetic foot ulcers

Abstract: Diabetic foot ulcers (DFUs) are a serious complication of diabetes that results in significant morbidity and mortality. Mortality rates associated with the development of a DFU are estimated to be 5% in the first 12 months, and 5-year morality rates have been estimated at 42%. The standard practices in DFU management include surgical debridement, dressings to facilitate a moist wound environment and exudate control, wound off-loading, vascular assessment, and infection and glycemic control. These practices are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
403
0
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(497 citation statements)
references
References 102 publications
4
403
0
25
Order By: Relevance
“…It is worth noting that keratinocytes contain the enzymatic set capable to form esters. In the present observational blinded study, we recognised that this new topical formulation induced a rapid wound healing compared to topical administration of hyaluronic acid (2%) . Currently, Qu and related flavonoids are well‐known phosphatidylinositol 3 kinase (PI3‐kinase), xanthine oxidase, cyclooxygenase inhibitors, and GPR40 agonist; therefore has anti‐inflammatory anti‐plateles and antiedematous effects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is worth noting that keratinocytes contain the enzymatic set capable to form esters. In the present observational blinded study, we recognised that this new topical formulation induced a rapid wound healing compared to topical administration of hyaluronic acid (2%) . Currently, Qu and related flavonoids are well‐known phosphatidylinositol 3 kinase (PI3‐kinase), xanthine oxidase, cyclooxygenase inhibitors, and GPR40 agonist; therefore has anti‐inflammatory anti‐plateles and antiedematous effects.…”
Section: Discussionmentioning
confidence: 95%
“…DFUs are a prevalent complication of DM and the International Diabetes Federation reports that 9.1 to 26.1 million patients develop DFUs annually Walsh et al, described that patients with DFU have a 5% mortality in the first 12 months, 42% within 5 years, and a 2.5‐fold increased risk of death compared with diabetic patients without foot ulcers. Although the principles that guide the standard of care are rigorous, there is still a significant gap between our current and desired wound healing outcomes . In this study, we evaluated the effects of a new compound (nano‐hydrogel embedded with Qu and OA) in the management of DFU.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, numerous DFU literatures mentioned the term of ‘ management ’ , which may possibly give rise to confusion regarding the understanding of the term, ‘ care ’. Consequently, we also then explored and revealed that ‘management ’ is a universal concept that has been used in many disciplines, not only in the health sciences.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetic foot ulcer (DFU) is described as a full‐thickness lesion appearing at the skin of the foot along with infection, destruction of tissues due to neuropathy and/or peripheral artery disease (PAD) in people with diabetes . The International Diabetes Federation states that 9.1 to 26.1 million people with diabetes will suffer DFU each year . In regard to long‐term conditions, DFU may ultimately prompt lower extremity amputation (LEA), thus declining patients’ quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…However, many patients with end stage CAD or PAD are not candidates for such procedures due to a lack of target vessels. On the other hand, standard treatment of diabetic foot ulcers is purely supportive . Therapeutic angiogenesis, that is, the generation of new vascular networks through delivery of specific growth factors, is an attractive strategy to restore perfusion to ischemic tissues and fill this unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%